2014
DOI: 10.1371/journal.pone.0093638
|View full text |Cite|
|
Sign up to set email alerts
|

The Muscle Ankyrin Repeat Proteins CARP, Ankrd2, and DARP Are Not Essential for Normal Cardiac Development and Function at Basal Conditions and in Response to Pressure Overload

Abstract: Ankrd1/CARP, Ankrd2/Arpp, and Ankrd23/DARP belong to a family of stress inducible ankyrin repeat proteins expressed in striated muscle (MARPs). The MARPs are homologous in structure and localized in the nucleus where they negatively regulate gene expression as well as in the sarcomeric I-band, where they are thought to be involved in mechanosensing. Together with their strong induction during cardiac disease and the identification of causative Ankrd1 gene mutations in cardiomyopathy patients, this suggests the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 50 publications
1
52
0
Order By: Relevance
“…Previous reports of deletion of one or all of the MARPs have detected minor effects. 6,7,19 The present findings in ischemic flaps and excisional wounds are highly consistent with the concept that ANKRD1 abundance becomes a rate-limiting factor when cells and tissues are challenged by injury and stress.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous reports of deletion of one or all of the MARPs have detected minor effects. 6,7,19 The present findings in ischemic flaps and excisional wounds are highly consistent with the concept that ANKRD1 abundance becomes a rate-limiting factor when cells and tissues are challenged by injury and stress.…”
Section: Discussionsupporting
confidence: 89%
“…16 Deletion of all three MARPs provides evidence of skeletal muscle weakness, 6 but the mouse strains in that study showed no developmental abnormalities, as in this report, or, in a more recent report, response to cardiac pressure overload. 7 …”
Section: Discussionmentioning
confidence: 99%
“…Ablation of all forms of muscle ankyrin repeat proteins (MARPs), including CARP, enhances the MyoD and MLP expression in skeletal muscle (23). While ablation of CARP or MARPs has been shown to not affect the cardiac function similar to our Mypn Q526X homozygotes (24), cardiac-restricted CARP over-expression results in an inhibition of hypertrophic and fibrotic remodeling via reduced TGF-ÎČ and ERK1/2 (18). Our previous Mypn Y20C transgenic mouse model ( Central Illustration ) suggested a crucial role of nuclear WT-Mypn by demonstrating the development of hypertrophic cardiomyopathy in vivo as a result of perturbed nuclear shuttling of Mypn (9).…”
Section: Discussionmentioning
confidence: 51%
“…They discovered that CARP Tg mice developed less hypertrophy than wild-type mice in cardiac hypertrophy models, including transverse aortic constriction (TAC) and isoproterenol, and concluded that CARP could attenuate cardiac hypertrophy mediated by inhibition of extracellular signal-regulated protein kinases 1 and 2 (ERK1/2) and transforming growth factor ÎČ (TGF-ÎČ) pathways and then decrease fibrosis deposition in the heart. Conversely, Bang et al (2014) found that CARP is not essential for normal cardiac development and functions in basal conditions and in response to mechanical pressure overload; Chen et al (2014) demonstrated that CARP promoted cardiomyocyte hypertrophy through calcineurin accumulation.…”
Section: Cardiac Hypertrophymentioning
confidence: 99%